Making high quality care an organisational strategy: Results of a longitudinal mixed methods study in Australian hospitals. (August 2021) - Balding, Cathy; Leggat, Sandra
Significant resources are spent on monitoring and improving the quality and safety of hospital care; however, evidence suggests that this investment is achieving disproportionately limited results. Accreditation and expectations of funders have focused hospital service quality management on compliance, with an over emphasis on the 'control' aspect of Juran's Quality Trilogy. This study compared the impact of the implementation of a strategic quality management system with existing compliance-focused quality management systems in a sample of Australian hospitals. Through action research, mixed methods data were tracked and compared implementation progress and outcomes between four experimental and four control hospitals from 2015 to 2017. While three years was not enough time to observe quality changes resulting from the implementation, three experimental hospitals made high quality care a strategic priority for their organisation and developed organisation-wide processes to achieve it. These hospitals demonstrated that including a strategic quality planning component in quality system design and implementation, as advocated by Juran but absent in many hospital quality systems, was a positive lever for staff commitment to delivering consistently high quality care.